A CRITICAL REVIEW OF DENTISTS' ADHERENCE TO HEALTH ADMINISTRATION PROTOCOLS - Abdullah Hameed Alshammari, Yahya Hassan Ali Al Amer Asiri , Abeer Mohammed Hawsah, Abdulrahman Ahmed Alomairy, Abdulaziz Mohammed Bin Ghaith, MulhemAbdulah Alsubaie (Chelonian Research Foundation, 2023)
This article presents a comprehensive review of dentists' adherence to health administration protocols, highlighting the critical role that regulatory compliance plays in ensuring patient safety and quality care within dental practices. Through an in-depth analysis, we explore the various dimensions of compliance, including the established health administration standards, the methods employed by dentists to meet these requirements, the challenges faced, and the consequences of non-compliance. Innovations in technology and patient involvement are also examined as pivotal factors enhancing adherence to these protocols. By conducting a comparative analysis across different regions, this review uncovers the influence of cultural, economic, and legal factors on compliance rates and offers pragmatic recommendations for both practitioners and regulatory bodies to bolster compliance efforts. The findings of this review underscore the importance of a collaborative, informed approach to compliance in dentistry, advocating for continuous education, technological adoption, and patient engagement as key strategies for improving adherence to health administration protocols. Keywords: Dental Compliance, Health Administration Standards, Patient Safety, Quality Care in Dentistry, Regulatory Compliance, Technological Innovations in Dentistry, Patient Advocacy, Global Compliance Comparison, Continuous Education in Dentistry, Legal Challenges in Dental Compliance